2004
DOI: 10.1007/s00737-004-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

Do changes in mood and concerns about weight relate to smoking relapse in the postpartum period?

Abstract: SummaryThe majority of women who quit smoking during pregnancy will resume smoking during the postpartum period. Little is known, however, about the predictors of postpartum relapses to smoking. Changes in mood and increases in concerns about weight are common during the postpartum period, and these factors may affect women's postpartum smoking behavior. In this paper, we present a model of the relationship among mood, weight concerns and postpartum smoking. Data from previous postpartum relapse prevention tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…However, postpartum smoking relapse is common and considerably less is known about how to sustain tobacco smoking abstinence postpartum [80]. There are unique features of the postpartum period that suggest intervention targets for smoking relapse prevention [81] and the STARTS intervention, described in this report, is designed to address the stress, negative mood and concerns about weight that mediate smoking relapse postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…However, postpartum smoking relapse is common and considerably less is known about how to sustain tobacco smoking abstinence postpartum [80]. There are unique features of the postpartum period that suggest intervention targets for smoking relapse prevention [81] and the STARTS intervention, described in this report, is designed to address the stress, negative mood and concerns about weight that mediate smoking relapse postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, contrary to our hypotheses, depressive symptoms during the third trimester of pregnancy were not predictive of lower motivation for postpartum abstinence. It is worth noting, however, that levels of depressive symptoms toward the end of pregnancy are often high (34,35), and the lack of an association between mood and postpartum abstinence motivation during pregnancy may reflect that both motivated and unmotivated women reported considerable depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Because mild levels of depressive symptomatology have been associated with a resumption of smoking, independent of nicotine dependence (33), depressive symptoms also may decrease a woman's motivation to remain abstinent postpartum. Thus, both changes in mood and concerns about body shape and weight may play a role in women's attitudes toward smoking during the postpartum period (34). However, the relation between these factors and a pregnant woman's motivation for postpartum abstinence is not known.…”
Section: Introductionmentioning
confidence: 99%
“…We have documented that mood and weight concerns may be distinctly associated with postpartum relapse because of the particular psychosocial changes that accompany the postpartum period (Levine & Marcus, 2004). Moreover, we have found that smoking-related weight concerns at the end of pregnancy predict decreased motivation to remain abstinent from smoking postpartum (Levine, Marcus, Kalarchian, Weissfeld, & Qin, 2006).…”
Section: Introductionmentioning
confidence: 99%